2010
DOI: 10.1161/circep.110.945824
|View full text |Cite
|
Sign up to set email alerts
|

J Wave, QRS Slurring, and ST Elevation in Athletes With Cardiac Arrest in the Absence of Heart Disease

Abstract: Background-QRS-ST changes in the inferior and lateral ECG leads are frequently observed in athletes. Recent studies have suggested a potential arrhythmogenic significance of these findings in the general population. The aim of our study was to investigate whether QRS-ST changes are markers of cardiac arrest (CA) of unexplained cause or sudden death in athletes. Methods and Results-In 21 athletes (mean age, 27 years; 5 women) with cardiac arrest or sudden death, the ECG recorded before or immediately after the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
43
1
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(53 citation statements)
references
References 30 publications
4
43
1
3
Order By: Relevance
“…J-point elevation especially in precordial leads has been considered a benign, training related ECG finding (23). In contrast, early repolarization appearing in inferior or lateral leads, particularly if associated with the widening of the terminal part of the QRS called notching or slurring may be associated with sudden cardiac death (5,9). In our study, early repolarization was mainly observed in precordial leads.…”
Section: Discussionmentioning
confidence: 44%
“…J-point elevation especially in precordial leads has been considered a benign, training related ECG finding (23). In contrast, early repolarization appearing in inferior or lateral leads, particularly if associated with the widening of the terminal part of the QRS called notching or slurring may be associated with sudden cardiac death (5,9). In our study, early repolarization was mainly observed in precordial leads.…”
Section: Discussionmentioning
confidence: 44%
“…The same authors found in a general population a non-significantly slower HR in those with ER patterns, in both genders [7]. In the investigation of Cappato et al [8] athletes with J wave/QRS slurring had a HR of 57 ± 5, as compared to 61 ± 7 in those without. In the Pilot Finnish Athlete Population study HR was lower in subjects with ER ER -early repolarization; HR -heart rate (68 ± 1) than in those without (71 ± 1, p = 0.02).…”
Section: Discussionmentioning
confidence: 76%
“…11,14 A higher prevalence of J-wave and/or QRS slurring (but not of ST elevation) has been found among athletes with cardiac arrest/sudden death than in controls. 15 A horizontal/descending type (defined as ≤0.1 mV elevation of the ST segment within 100 ms after the J point) in the inferior leads, as opposed to a rapidly ascending ST segment type, may help to identify those individuals who are clearly at risk (see Figure 2). 16,17 Coexistence of an anterior early repolarisation pattern (e.g.…”
Section: Clinical Significancementioning
confidence: 99%
“…16,17 In the Atherosclerosis Risk in Communities (ARIC) study, J-point elevation was associated with an increased risk of sudden cardiac death (SCD) in whites and in women, but not in blacks or men. 20 A pattern of J-wave and/or QRS slurring (but not of ST elevation) has been associated with cardiac arrest/sudden death in athletes, 15 but many healthy athletes have early repolarisation with a rapidly ascending pattern. Inferolateral early repolarisation pattern is seen in 25-35 % of competitive athletes, and inferior only in 4 %, and is considered a dynamic phenomenon related to physical activity.…”
Section: Clinical Significancementioning
confidence: 99%